2014
DOI: 10.1136/archdischild-2014-306237.321
|View full text |Cite
|
Sign up to set email alerts
|

G338(P) Epilepsy alarm/monitor - Questionnaire survey of the Parent's perception of the use of the epilepsy alarm

Abstract: Introduction The risks due to epilepsy are reduced by good seizure control and staying safe. Parents of children with epilepsy often have sleepless nights in view of their concerns about night time seizures. There are different devices including different types of alarms/monitors available, and choosing the appropriate device among them depends on the type of seizure. Aim The aim of our survey was to review the various types of devices used by parents to monitor seizures and their perception and usefulness r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There is evidence suggesting that seizures could be identified using audio detection devices in at least 50% of individuals (8). A survey suggested that most parents found it useful to have some device, especially an audio monitor, to reduce stress and provide reassurance (9). There is no evidence to suggest that sophisticated monitoring systems are more sensitive to identify seizures than a simple audio device (10).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence suggesting that seizures could be identified using audio detection devices in at least 50% of individuals (8). A survey suggested that most parents found it useful to have some device, especially an audio monitor, to reduce stress and provide reassurance (9). There is no evidence to suggest that sophisticated monitoring systems are more sensitive to identify seizures than a simple audio device (10).…”
Section: Introductionmentioning
confidence: 99%